PEDAGOGICAL FOUNDATIONS FOR DEVELOPING CORRECT POSTURE AND BODY STRUCTURE IN PRESCHOOL CHILDREN THROUGH PHYSICAL EXERCISES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examines the issue of developing correct posture and body structure in preschool and early primary-aged children through physical exercises. It explores the causes of postural deviations and presents pedagogical strategies to address them. Proper posture—characterized by spinal health, balanced muscle development, and optimal cardiopulmonary function—is vital for children’s wellbeing. The paper analyzes corrective exercise routines and playful teaching methods to guide instructors in practical application.